Electrochemical effect of carbon nanospheres on an AB5 alloy - Cuscueta, Diego Javier (2012)
In this paper, the effect of the addition of carbon nanospheres (CNE) by high energy mechanical milling to the active material of the negative electrode of a NickeleMetal Hydride (NieMH) battery is studied. The hydrogen storage alloy (MH) is an AB5-type (Lm0.95Ni3.8Co0.3Mn0.3Al0.4), where Lm is a mixture of rare earths, and it was prepared by melting the constituent elements in an electric induction furnace. The CNE were synthesized by two-stage polymerization of furfuryl alcohol, drying and carbonization, and were subsequently doped with different proportions of Ni (0e20%) by the method of wet impregnation with Nickel nitrate hexahydrate. The behavior of electrochemical cells consisting of a working electrode with 45% of MH, 5% of CNE pure and doped with different proportions of Ni and 50% carbon Teflon acting as electrical and mechanical support, a counter electrode of Ni mesh, and a reference electrode Hg/HgO was studied. The experiments covered electrochemical activation and cycle stability, rate capability and electrochemical impedance spectroscopy. The results show that the addition of CNE improves the electrochemical performance, and particularly the CNEs pure and doped with 20% of Ni present the best electrochemical performance in discharge capacity, rate capability and impedance spectroscopy.